การศึกษาสภาพและปัญหาการจัดการเรียนการสอนสำหรับเด็กวัยอนุบาล ในโรงเรียนเมืองพัทยา สังกัดเมืองพัทยา - จุไรพร เสนาะ (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
To study state and problems of instructional management for preschool children in Pattaya public schools under the Pattaya City. The research emphasized on 3 areas : curriculum implementation, learning activities, and state and environmental management to support in classroom instruction. The data were collected from 449 subjects, including 10 school administrators, 49 kindergarten teachers and 390 preschool parents. The research data was collected through questionnaires,interview, observation, and surveying, The data were analyzed by frequency distribution and percentage. The findings of the study indicated that 1) Curriculum implementation. It was found that most teachers performed their teaching in terms of experience management set by local administration agency in cooperation with preschool curriculum BE. 2540. Most teachers were participated in planning the curriculum by giving information related to learning activities, In addition the curriculum was development by providing activities in accordance with children and local state. 2) Instructional activity. In the most schools, there were instructional planning school policy, specifying operational plan and budget allocation. The teachers, however had prepared themselves for media included both real objects and pictures, for lesson plans teaching, In most schools books were available at the classroom corner. Teachers measured and evaluated children development by observation. 3) State and environmental management to support instructional activities. There were personal preparation and development. Teachers were assigned according to their education qualifications. Orientations and seminar were conducted for personal benefits. Non -formal supervisor unit with in schools were set up. Administrators acted as teaching supervisors. Materials, curriculum and media supplied. Surrounding and learning sources, were specifically provided in special rooms. Playgrounds were available. Facilities, break and lunch services were supplied. Parents supported school activities through donations. The problems included teacher s lack of curriculum understanding, inadequate budget and personal, and non system and discontinue of teaching supervision. Insufficient and non-specified playgrounds were also reported